How to encounter the child in coma - Mohammad Hassan Aelami (Reviews in Clinical Medicine, 2014)
Non-traumatic coma is a medical emergency and should be evaluated as soon as possible. Pediatric coma is more serious because of patient’s capacity of pathological stressor tolerance is limited especially in neonates. Several etiologies could be listed for loss of consciousness (LOC) and coma in childhood. According to the epidemiological studies, causes of coma are different all around the world. Glasgow Coma Scale has been used for coma scaling. In this review, we focused on some highlight causes of coma in pediatric medicine.